2011
DOI: 10.1073/pnas.1103457108
|View full text |Cite
|
Sign up to set email alerts
|

Genes involved in convergent evolution of eusociality in bees

Abstract: Eusociality has arisen independently at least 11 times in insects. Despite this convergence, there are striking differences among eusocial lifestyles, ranging from species living in small colonies with overt conflict over reproduction to species in which colonies contain hundreds of thousands of highly specialized sterile workers produced by one or a few queens. Although the evolution of eusociality has been intensively studied, the genetic changes involved in the evolution of eusociality are relatively unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
225
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(240 citation statements)
references
References 39 publications
10
225
1
2
Order By: Relevance
“…African and European bees differed in the AST gene encoding the juvenile hormone-inhibiting allatostatin, an Ih-like dopamine regulator, and the genes for several odorant receptors. We detected a nonsynonymous variant in the neuronal gene RhoGAP100F (Rho GTPase-activating protein at 100F), which evolves rapidly in highly social insect lineages 35 . We found highly differentiated SNPs in the exonic regions of key genes in the insulin-vitellogenin signaling pathway, which is important for queen longevity and for worker labor division 36 , including a large number of highly differentiated SNPs in the 3′ UTR of IhR (encoding the insulin-like receptor) and nonsynonymous SNPs in the foxo (forkhead box, subgroup O), Vg (vitellogenin) and yl (vitellogenin receptor) genes ( Supplementary Fig.…”
Section: Genes Under Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…African and European bees differed in the AST gene encoding the juvenile hormone-inhibiting allatostatin, an Ih-like dopamine regulator, and the genes for several odorant receptors. We detected a nonsynonymous variant in the neuronal gene RhoGAP100F (Rho GTPase-activating protein at 100F), which evolves rapidly in highly social insect lineages 35 . We found highly differentiated SNPs in the exonic regions of key genes in the insulin-vitellogenin signaling pathway, which is important for queen longevity and for worker labor division 36 , including a large number of highly differentiated SNPs in the 3′ UTR of IhR (encoding the insulin-like receptor) and nonsynonymous SNPs in the foxo (forkhead box, subgroup O), Vg (vitellogenin) and yl (vitellogenin receptor) genes ( Supplementary Fig.…”
Section: Genes Under Selectionmentioning
confidence: 99%
“…Further highly differentiated coding SNPs were found in many innate immune defense genes within the Toll and JAK-STAT pathways, including pll (pelle) and several serine proteases. pll was earlier detected as being quickly evolving in social insects 35 . Among the top coding A versus MC SNPs, we also detect significant (P = 0.012) enrichment for genes involved in platelet plug formation, which is activated to heal wounds and form infection barriers in insects 44 , including Hml (hemolectin) (Supplementary Fig.…”
Section: Genes Under Selectionmentioning
confidence: 99%
“…Therefore, identifying the molecular mechanisms common to both origins of eusociality is crucial to understanding the fundamental signatures of these rare evolutionary transitions. While the availability of genomes from many eusocial and non-eusocial hymenopteran species 8 has allowed extensive research into the origins of eusociality within ants and bees [9][10][11] , a paucity of genomic data from cockroaches and termites has precluded large-scale investigations into the evolution of eusociality in this hemimetabolous clade.The conditions under which eusociality arose differ greatly between the two groups. Termites and cockroaches are hemimetabolous and so show a direct development, while holometabolous hymenopterans complete the adult body plan during metamorphosis.…”
mentioning
confidence: 99%
“…This study analyzed ∼3,600 genes from a set of 10 social and nonsocial bee transcriptomes; these species encompass three independent origins of eusociality (21). Hundreds of genes were identified that exhibit a molecular signature of rapid evolution associated with sociality, defined as a higher ratio of nonsynonymous-to-synonymous nucleotide substitutions (d N /d S ) in social relative to nonsocial bee lineages (21). Throughout this review, evidence for rapid evolution is based on relative d N /d S and positive selection is defined as d N /d S > 1, unless otherwise specified.…”
mentioning
confidence: 99%